Evolutionary Origins of Drought Tolerance in Spermatophytes - Bowles, Alexander M. C.; Paps, Jordi; Bechtold, Ulrike (Frontiers in Plant Science, 2021)
It is commonly known that drought stress is a major constraint limiting crop production. Drought stress and associated drought tolerance mechanisms are therefore under intense investigation with the view to future production of drought tolerant crops. With an ever-growing population and variable climate, novel approaches need to be considered to sustainably feed future generations. In this context, definitions of drought tolerance are highly variable, which poses a major challenge for the systematic assessment of this trait across the plant kingdom. Furthermore, drought tolerance is a polygenic trait and understanding the evolution of this complex trait may inform us about patterns of gene gain and loss in relation to diverse drought adaptations. We look at the transition of plants from water to land, and the role of desiccation tolerance in enabling this transition, before discussing the first drought tolerant plant and common drought responses amongst vascular plants. We reviewed the distribution of a combined “drought tolerance” trait in very broad terms to encompass different experimental systems and definitions used in the current literature and assigned a binary trait “tolerance vs sensitivity” in 178 extant plant species. By simplifying drought responses of plants into this “binary” trait we were able to explore the evolution of drought and desiccation tolerance across the wider plant kingdom, compared to previous studies. We show how this binary “drought tolerance/sensitivity” trait has evolved and discuss how incorporating this information into an evolutionary genomics framework could provide insights into the molecular mechanisms underlying extreme drought adaptations.treme drought adaptations.